Acute hemorrhagic leukoencephalitis manifesting as intracerebral hemorrhage associated with herpes simplex virus type I - Kabakus, N; Gurgoze, MK; Yildirim, H; Godekmerdan, A; Aydin, M (Oxford Univ Press, 2005)
Acute hemorrhagic leukoencephalitis (AHL) is a rare and usually fatal disorder characterized by an acute onset of neurological abnormalities. It may occur in association with a viral illness or vaccination. Radiology and brain biopsy are essential for the diagnosis. We present a case of AHL mimicking or manifesting as intracerebral hemorrhage associated with herpes simplex virus. A 3-year-old boy was admitted to our hospital with cerebral hemorrhage. The findings of cerebrospinal fluid, MRI and electroencephalogram indicated acute hemorrhagic leukoencephalitis associated with herpes simplex virus involving the left parietal cortex (hemorrhage) and the right temporal lobe (encephalitis). The patient received intravenous dexamethasone (1.5 mg/kg/24 h divided q6 (six times a day) for 5 days, tapered slowly to discontinuation over the next 5 days) and aciclovir (15 mg/kg/every 6 h for 14 days). His clinical condition markedly improved, and after 3 weeks he was discharged from the hospital with moderate right hemiparesis. Mild hemiparesis with normal psychometric testing was determined when he was checked 6 months later. AHL remains misdiagnosed as viral encephalitis because it produces different protean clinical forms. Pediatric patients admitted with cerebral hemorrhage and infarct should be evaluated for presence of hemorrhagic encephalitis-causing agents, especially for herpes simplex. Since, as in our case, treatment with corticosteroid and acyclovir markedly improves conditions of herpes simplex-caused AHL, we suggest that early diagnosis and treatment is of importance for the prognosis.
Keywords: Recovery